How do you solve \( \frac{1}{2} \log _{a}(x+2)+\frac{1}{2} \log _{a}(x-1)=\frac{2}{3} \log _{a} 27 \)
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Mind Expander
To solve the equation \( \frac{1}{2} \log _{a}(x+2)+\frac{1}{2} \log _{a}(x-1)=\frac{2}{3} \log _{a} 27 \), you can start by simplifying the left side using the property of logarithms that states \( \frac{1}{2} \log_a b = \log_a b^{1/2} \). This means you can rewrite the left side as: \[ \log_a \sqrt{x+2} + \log_a \sqrt{x-1} = \log_a (\sqrt{x+2} \cdot \sqrt{x-1}) = \log_a \sqrt{(x+2)(x-1)} \] Now we tackle the right side. The expression \( \frac{2}{3} \log_a 27 \) can be rewritten as \( \log_a (27^{2/3}) \). Since \( 27 = 3^3 \), we have \( 27^{2/3} = 3^2 = 9 \). Now the equation looks like this: \[ \log_a \sqrt{(x+2)(x-1)} = \log_a 9 \] Since the logarithms on both sides are equal, you can equate their arguments: \[ \sqrt{(x+2)(x-1)} = 9 \] Squaring both sides gives: \[ (x+2)(x-1) = 81 \] Expanding this leads to: \[ x^2 + 2x - x - 2 = 81 \quad \Rightarrow \quad x^2 + x - 83 = 0 \] Now, use the quadratic formula, \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 1, b = 1, c = -83 \): \[ x = \frac{-1 \pm \sqrt{1^2 - 4 \cdot 1 \cdot (-83)}}{2 \cdot 1} = \frac{-1 \pm \sqrt{1 + 332}}{2} = \frac{-1 \pm \sqrt{333}}{2} \] This gives us two possible solutions. However, we must check which, if any, satisfy the domains of the logarithms, i.e., \( x+2 > 0 \) and \( x-1 > 0 \) implying \( x > 1 \). Therefore, checking the resulting values will confirm valid solutions. Now you can find the approximate numerical values of these roots for the final verdict! Happy solving!